The relationship between work life balance and job satisfaction among staff at Sarawak Skills Development Centre (SSDC) / Muhammad Harris Shukor - Shukor, Muhammad Harris (2018)
The purpose of this study is to identify the relationship between work life balance and job satisfaction in Sarawak Skills Development Centre (SSDC). Work flexibility implies not only variation in time and place of the job, but also sharing of the job, career breaks (maternity/paternity leaves), part-time and term-time working. While employees’ wellness program define as business win with decrease tangible cost in the area of healthcare, inability, absenteeism and worker’s compensation. As for employee satisfaction, it is a measure of how cheerful workers are with their activity and workplace. The approach that have been used is distributing questionnaires to the staff of Sarawak Skills Development Centre (SSDC). The questionnaires were distributed to 120 participants. However, only 92 participants responded to the questionnaires that were distributed to the staff. Based on the results, the independent variables, Flexible Working Hours and Wellness Program have strong relationship with Job Satisfaction. Flexible Working Hours shows a very significant strong positive relationship with Job Satisfaction with (r=.561).Surprisingly, the results revealed that Wellness Program also shows a very significant strong positive relationship between Job Satisfaction with the value of (r=.557). Thus, it is proven that Flexible Working Hours and Wellness Program have strong relationship with Job Satisfaction.